Synthesis, Characterization, Molecular Docking and Cytotoxicity Studies of Bagasse Xylem Ferulate-Acrylamide/Methyl Methacrylate Composite - Kai Zuo; Jingxia Qian; Jun Gong; Jun Zhang; Heping Li; Guoyong Zhou (Iranian Journal of Chemistry & Chemical Engineering, 2019)
BXFL (bagasse xylem ferulate)-g-AM (acrylamide)/MAA (methyl methacrylate) was synthesized based on bagasse xylan(BX)-g-AM/MAA in 1-Butyl-3-methylimidazolium chloride ([Bmim] Cl) ion solution with Ferulic Acid (FL) as esterification agent. The various factors that were investigated influenced carboxylic acid ester substitution degree (DSC) of BXFL-g-AM/MAA. The structures of BXFL-g-AM/MAA were confirmed by IR, SEM and 1H NMR analysis. The cytotoxicity of BXFL-g-AM/MAA was investigated against twelve kinds of protein through Surflex-Dock Mode of Sybyl-X 2.0 software, and on three kinds of human cancer cells line and the human normal cells line were detected by MTT assay. It was shown that the maximum DSC was 1.09 in ion solution, which was superior to DSC of conventional method in organic solvent. The results of MTT assay were consistent with docking results. BXFL-g-AM/MAA exhibited relative high cytotoxicity against human gastric cancer cells (MGC-803) line.